2008
DOI: 10.1002/jso.21139
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of circulating endothelial progenitor cells in head and neck cancer patients

Abstract: In this pilot study CD133(+)/KDR(+) EPCs were significantly elevated in head and neck tumor patients before and after therapy. Our results warrant further studies on the use of EPCs as a surrogate marker for anticancer therapies in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Since CECs are rare events, their precise quantification in peripheral blood (PB) samples requires a technically rigorous analytical approach, which should take many factors into consideration (8). Several pre-analytical and analytical steps significantly affect not only the quantification of CECs, but can also result in a change in the definition of these cells, leading to problems in the interpretation of the results (Table I) and in their potential association with clinical endpoints (Table II) (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Flow Cytometric Analysis Of Circulating Endothelial Cells Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Since CECs are rare events, their precise quantification in peripheral blood (PB) samples requires a technically rigorous analytical approach, which should take many factors into consideration (8). Several pre-analytical and analytical steps significantly affect not only the quantification of CECs, but can also result in a change in the definition of these cells, leading to problems in the interpretation of the results (Table I) and in their potential association with clinical endpoints (Table II) (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Flow Cytometric Analysis Of Circulating Endothelial Cells Inmentioning
confidence: 99%
“…In many previous studies, CECs are identified as those positive for a nuclear binding fluorochrome, negative for the leukocyte marker, cluster of differentiation (CD)45, and positive for CD31 and CD146 (25,28,(30)(31)(32)(33)(34). Previously, the expression of CD109, a cell surface glycoprotein which has been shown to be overexpressed in tumor endothelial cells, has been utilized to identify a specific subpopulation of CECs potentially useful as a prognostic marker in specific tumor types (35).…”
Section: Flow Cytometric Analysis Of Circulating Endothelial Cells Inmentioning
confidence: 99%
“…68 Consistent with their role in tissue regeneration, EPCs are also recruited when the tumor vasculature is destroyed by chemo/radiation therapy, both in preclinical models as well as in clinical studies. [69][70][71] 74 and why EPC levels rebound in glioblastoma patients during drugfree intervals of a pan-VEGF inhibitor. 25 In breast cancer patients during drug-free intervals after chemotherapy, EPCs increase similarly, concomitant with a rise of plasma VEGF and other pro-angiogenic cytokines.…”
Section: Role Of Endothelial (Progenitor) Cells In Anti-angiogenic Esmentioning
confidence: 99%
“…Numerous studies that only used FACS technique have been conducted to reveal the dynamics of CEPCs in various cancer types such as lung cancer [22,[52][53][54], malignant glioma [20,55,56], HCC [21,57], breast cancer [58,59], head and neck cancer [60], ovarian cancer [61][62][63], cervical cancer [63], colorectal cancer [64], prostate cancer [65], renal cell carcinoma (RCC) [66,67], osteosarcoma [68], and multiple myeloma [69] (Table 1). However, inconclusive and controversial results were obtained; although in most studies, a significantly higher EPCs concentration was observed in the peripheral blood of cancer patients.…”
Section: Circulating Levels Of Epcs In Cancer Patientsmentioning
confidence: 99%
“…However, the assessment of these parameters cannot reflect the efficacy immediately and directly, thus necessitating a reliable surrogate biomarker. The potential of CEPCs in the prediction and response monitoring to a therapeutic intervention is determined by distinguishing the impact of various interventions (e.g., surgery, chemotherapy, and radiation) on CEPCs in different cancers, including breast cancer [59,72], head and neck cancer [60], lung cancer [22,54,76], ovarian cancer [61,63], RCC [66,67], colorectal cancer [79], multiple myeloma [69], glioma [56], gastric cancer [74], and mixed types [75] (Table 3). In all studies, the CEPCs levels were quantified by FACS technique, which are not presented in Table 3.…”
Section: Cepcs As An Indicator Of Treatment Responsementioning
confidence: 99%